Forecasting Inflation via Experimental Stock Markets: Some Results from Pilot Markets - Michael Berlemann; Forrest Nelson (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2005)
While there are various techniques of inflation forecasting in use, none of them has proved to deliver consistently more accurate forecasts than the others. That is why most users of inflation forecasts monitor a variety of inflation indicators and forecasts and check them for consistency. This paper aims at contributing to an extension of themethods in use. We propose to conduct experimental inflation forecasting markets in order to uncover market participants' inflation expectations. While the markets directly deliver density forecasts of inflation they also allow to construct mean forecasts and a measure of forecast uncertainty. We also present evidence from a number of pilot markets underlining that the proposed method might enrich the arsenal of existing forecastingtechniques.
Keywords: E58; F15; F33; 330; Inflation forecast; field experiments; experimental stock markets